Hypothyroidism and Muscle Pseudohypertrophy: Kocher-Debre Semelaigne Syndrome - Tolga Altuğ Şen; Hafza Uçar; Gülay Gün; Faruk Alpay; Özlem Güraksın; Tevfik Demir; Reşit Köken; Hamide Melek (Güncel Pediatri)
Long standing hypothyroidism without therapy leads to myopathy which is associated with proximal muscle weakness, fatigue, exertional pain, pseudohypertrophy due to myoedema, diminished deep tendon reflexes, and stiffness in muscles. Kocher-Debre-Semelaigne syndrome is a specific, rare form of hypothyroid myopathy, which causes hypertrophy of muscles. In this article, we emphasized hypothyroid myopathy by reporting a-13 4/12-year old girl with short stature who was diagnosed with hypothyroidism due to thyroid aplasia that caused pseudohypertrophy of muscles. (Journal of Current Pediatrics 2009; 7: 37-40)